Optimal Skin Prick Test Panel for Detecting Respiratory Allergens in Children: A Retrospective Study - Aykut Eşki; Gökçen Kartal Öztürk; Figen Gülen; Esen Demir (Journal of Pediatric Research)

(untitled)
Aim:The skin prick test (SPT) is the standard tool for determining respiratory allergen sensitizations. Different allergen sensitization patterns have been observed within countries and regions according to geographical and seasonal variations. This study aims to identify the sensitization pattern of children in different age groups and to define the minimum number and type of allergen extracts in an SPT to detect a sensitized child.Materials and Methods:This retrospective study was conducted in the Outpatient Clinic of the Pediatric Allergy, Immunology, and Pulmonology Unit of a tertiary Children’s Hospital from October 2019 to December 2020. Children aged between 2 and 18 years suspected of inhalant allergy with the presence of clinically relevant symptoms were included. The results of SPT were collected from medical records to determine the optimal panel to cover 95% of the sensitized children.Results:A total of 1821 patients with SPT results were evaluated. Forty-three patients (2.4%) were excluded from the study because some allergen extracts did not apply. Consequently, 1778 children (male/female ratio of 1.33) were included in the study. The median age (interquartile range) was 8 years (2-18). The most common sensitizations were to grasses (Lolium perenne and Poa pratensis), trees (Olea europaea and Fraxinus excelsior), cereals (Avena sativa and Hordeum vulgare), animal dander (cat and dog), and weeds (Plantago lanceolata and Ambrosia artemisiifolia). The rate of sensitization tended to increase with age. Applying an SPT that included six allergen extracts for 2-5 years, five for 6-11 years, and four for 12-18 years was sufficient to identify 95% of sensitized children.Conclusion:A test panel with six allergen extracts was sufficient to identify most of the sensitized children and adolescents suspected of allergy and had clinically relevant symptoms. An SPT with fewer allergen sources was required to detect older sensitized children than younger children.